The Role of Community Learning Center Managers in The Development of Womens Productive Economic Businesses (Edukasi, 2022)
The purpose of this study is to describe the efforts of the managers of the Al Barokah Smart House in developing women's productive economic enterprises in society. The method used in this research is descriptive research method with a qualitative approach. The techniques used in this research are interviews, observation and documentation study. The subjects in this study were five people. The results of this study indicate that in developing productive economic enterprises, managers make efforts including facilitating the community, especially women in forming productive economic businesses, educating and teaching economic business processing skills, building networks and obtaining resources and marketing and optimizing women's productive economic enterprises. through various online marketing efforts. The conclusion of the study shows that the management's efforts in empowering the women's economy still need to be improved by building wider networks and adequate marketing access to be able to increase the economic independence of families in the communities around the Al Barokah Smart House